SISTEM PENDUKIUNG KEPUTUSAN PADA SISTEM SELEKSI PENERIMAAN GURU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Nurjaya Nurjaya; Maulana Ardhiansyah; Rezki Suryana (KILAT, 2018)
Teacher is an important element in the support system, therefore function and position of teachers in improving the quality of learners need to be considered seriously. Basically, teachers are professionals in the field of education that has the task of teaching, educating, and guiding students to become a man is impersonal. Thus, teachers have an important position and responsibilities of a very great deal in the success or failure of educational programs. In order to facilitate the selection process for the teachers, the school can use the Decision Support System Decision Support System that is used as a tool for decision makers to expand the capabilities of the decision makers, but not to replace the judgment of the decision makers. The method used is the Simple Additive weighting, Simple Additive Weighting (SAW) suitable for decision-making process because it can determine the weight values ​​for each attribute, followed by indexing process that will select the best alternative from a number of the best alternative. It can be concluded from this study that the SAW method is very relevant to solve the problem of decision makers.